Promoting and Regulating Cellular Agriculture in Malaysia and Indonesia: Analysing the Adequacy of the Regulatory Framework - Hasmin, Nor Akhmal; Tarigan, Vita Cita Emia; Yulida, Devi (Faculty of Law, Universitas Negeri Semarang, 2026)
Cellular agriculture is a nascent manufacturing technology that holds significant potential to strengthen global food security. Globally, the number of food manufacturing companies producing food using cellular agriculture is rapidly increasing. Products of cellular agriculture are also available for consumers in the marketplace. Hence, the objective of this study is to analyse the extent to which the food regulatory framework in Malaysia and Indonesia is ready to promote and regulate products and activities of cellular agriculture. The analysis is essential as cellular agriculture poses opportunities and regulatory challenges. Despite the benefits, it also poses potential safety and health risks to the consumers, owing to its novelty. This study adopts a doctrinal legal analysis by analysing the adequacy of the current food regulatory framework, i.e., national food policies and legislation in Malaysia and Indonesia. It is found that cellular agriculture is not part of the national food policy and food regulatory framework in Malaysia and Indonesia. Both jurisdictions are lacking regulatory preparedness to embrace the presence of products of cellular agriculture in the marketplace. Hence, there is a need to reform the current food regulatory framework. Such reform includes the formulation of national policy for cellular agriculture to promote the adoption of cellular agriculture in food manufacturing. The current food safety legislation also needs to be amended to incorporate the provisions to regulate the safety aspects.